Condutividade elétrica complexa de rochas - ROCHA, Brígida Ramati Pereira da (Universidade Federal do Pará, 2014)
Laboratory measurements of complex conductivity were made on 28 drill-core samples from area MM1-Prospect 1 of the Carajás Mining District. The objective of this research was to help interpret field geophysical survey of the area using Induced Polarization and AFMAG methods. The laboratory measurements of amplitude and phase of conductance were taken in the frequency interval of 10-3Hz to 104Hz. The method used was the direct measurement of impedance using a memory osciloscope, a signal generator, and two high input impedance differential preamplifiers. The electrode system chosen for the measurements was the 2 electrode platinized-platinum because its frequency response is flat in the frequency range used. AlI the measurements were made at a constant temperature of 24°C±1°C. A petrographic study of the samples was done, using thin sections, polished sections and X-ray diffraction. Copper content, in the form of sulfides, was determined using atomic absorption. As a result of the petrographic study, the samples were classified in five distinct groups: granite, biotite schist, amphibolite and magnetite quartzite-iron formation. The grade of Cu was variable in the five groups, ranging from 50 ppm to 6000 ppm. In the conductivity measurements it was observed that, among the five groups, the samples of iron formation gave the largest variations with frequency. The granite samples had spectra flatter than those of schist or amphibole. In conclusion, these measurements show that the field Induced Polarization and AFMAG anomalies near these three drill holes (F1, F2 and F3) are due primarily to the magnetic iron formation, and secondarily due to associated low-grade chalcopyrite mineralization.